2020
DOI: 10.1007/s11661-020-05711-6
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Diffraction-Based Strain with Macroscopic Stresses in Laser Powder Bed Fused Ti-6Al-4V

Abstract: The laser powder bed fusion (LPBF) production process often results in large residual stress (RS) in the parts. Nondestructive techniques to determine RS are badly needed. However, a reliable quantification of macro-RS (i.e., stress at the component level) by means of diffraction-based techniques is still a great challenge, because the link between diffraction-based strain and macro-RS is not trivial. In this study, we experimentally determine (by means of in-situ synchrotron radiation diffraction) this link f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The AM Ti6Al4V alloy seems to deviate from this behavior: Mishurova et al [156] showed, that for low H 2 (prismatic planes) the model predictions by Kröner agreed better with experimental data than other schemes (Figure 12c). In contrast, for higher H 2 (basal planes) the model prediction of Reuss better matched with the data [156]. This can be explained by the transverse isotropy of the single crystal elastic tensor, exhibiting an isotropic behavior in the basal directions but a strong anisotropy along its c-axis.…”
Section: Experimental Determination Of Diffraction Elastic Constantsmentioning
confidence: 86%
See 2 more Smart Citations
“…The AM Ti6Al4V alloy seems to deviate from this behavior: Mishurova et al [156] showed, that for low H 2 (prismatic planes) the model predictions by Kröner agreed better with experimental data than other schemes (Figure 12c). In contrast, for higher H 2 (basal planes) the model prediction of Reuss better matched with the data [156]. This can be explained by the transverse isotropy of the single crystal elastic tensor, exhibiting an isotropic behavior in the basal directions but a strong anisotropy along its c-axis.…”
Section: Experimental Determination Of Diffraction Elastic Constantsmentioning
confidence: 86%
“…When, on the contrary, the columnar as-built microstructure (exhibiting relatively strong crystallographic texture) was retained, the model prediction of Reuss best fit the experimental data for Inconel 718 and 625 (Figure 12a,b) [39,131]. The AM Ti6Al4V alloy seems to deviate from this behavior: Mishurova et al [156] showed, that for low H 2 (prismatic planes) the model predictions by Kröner agreed better with experimental data than other schemes (Figure 12c). In contrast, for higher H 2 (basal planes) the model prediction of Reuss better matched with the data [156].…”
Section: Experimental Determination Of Diffraction Elastic Constantsmentioning
confidence: 91%
See 1 more Smart Citation
“…The correct determination of the magnitude of residual stresses is expected to be crucial for the understanding of the mechanical performance of components. In this regard, the DEC measured in a LPBF Ti-6Al-4V alloy have been already reported to deviate from the DEC values of conventionally produced Ti-6Al-4V [27]. Note that the need to assess the validity of conventional DEC is not exclusive to AM materials, since this requirement is valid for any new material exhibiting unconventional microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…By adapting the scan strategy during the production of the AM samples, the impact of texture on the residual stress measurements can be minimized, at least within the near-surface region. [43][44][45] Other issues encountered in XSA analysis of AM samples include surface roughness and internal flaws, such as porosity and lack of fusion, as addressed in several recent studies. [46][47][48] In the case of laboratory measurements in reflection mode, the influence of such aspects is much more pronounced due to the lower information depth (penetration depth) of the beam and the resulting smaller gauge volume (e.g., depending on the wavelength of the beam, the angle of incidence, and the material under investigation).…”
Section: Challenges For Diffraction Experimentsmentioning
confidence: 99%